(untitled) (Global Journal of Human-Social Science, 2013)
The article compares two approaches that attempt to explain the socio-economic events and policy within states and global society: the Coloniality of Power and Cosmopolitanism. The article reconstructs the discourse of both of these theoretical perspectives to continue next with an assessment of their strengths and weaknesses. In a third stage, the article compares the commonalities and disagreements between the two. We conclude that the two paradigms make significant contributions, and that the social researcher has the important challenge of articulating both of them coherentlyin order to account for a concrete reality.